Peripheral Arterial Disease in Diabetes: Is There a Role for Genetics? - Katwal, Arabindra B. (2011)
Atherosclerotic occlusion of vessels outside of the heart is commonly referred to as peripheral arterial disease (PAD). The lower extremity is the most common site of PAD and its development is associated with the same risk factors involved in general atherosclerosis. However, there is emerging evidence that other risk factors may play a key role in the development of PAD. Over the past decade polymorphism in a number of genes has been shown to contribute to the risk of developing PAD. These genes can be classified into proartherosclerosis or proatherothrombosis based on the known gene function. Moreover, they can be categorized as “novel” polymorphism when the function of the genes is not known or when the specific gene within an associated genetic locus is not known. It is intriguing that not only are gene polymorphisms associated with PAD being identified, but more recently studies are now finding gene polymorphisms that may be important in development of this syndrome only in the contest of certain environmental factors such as diabetes. Currently how these gene–environment interactions contribute to the pathogenesis of PAD is poorly understood but will likely play a critical role in future understanding of this complex disease.